Spondyloepiphyseal dysplasia tarda with progressive arthropathy - Kaptanoğlu, Ece; Perçin, Ferda; Perçin, Sıtkı; Törel-Ergür, Ayça (The Turkish Journal of Pediatrics, 2004)
Spondyloepiphyseal dysplasia tarda with progressive arthropathy (SEDT-PA) is a rare autosomal recessive skeletal dysplasia affecting primarily the articular cartilage. Here we present a nine-year-old girl from Middle Anatolia (Sivas) with SEDT-PA. Her complaints were pain and progressive deformity of the joints. She had a short stature with increased thoracic kyphosis and lumbar lordosis. The range of motion was limited in the spine and the peripheral joints and she had deformities. Radiologic examination revealed generalized platyspondyly and irregularity of the vertebral endplates. There was minimal joint space narrowing at proximal interphalangeal joints, but there were no bone erosions. Metaphyses were widened and epiphyses were squared in other joints with generalized osteopenia and severe osteoarthritic changes prominent in hips. Laboratory examination revealed a mild increase in acute phase reactants. Genetic disorders like SEDT-PA may also have rheumatological involvement, so they should be kept in mind in differential diagnosis of inflammatory joint diseases.